Hambatan Guru Mengintegrasikan Nilai Karakter ke Mata Pelajaran Ekonomi di MAN 1 Nganjuk: Pendekatan Kualitatif Deskriptif: Penelitian - Tiara Nur’aini (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Character education is one of the important pillars in shaping individuals who are of integrity, moral, and responsible. This education aims to instill positive values such as honesty, discipline, cooperation, and empathy in daily life. However, the implementation of character education in Indonesia faces various complex obstacles, both from social, cultural, and systemic aspects. Factors such as the lack of alignment between the curriculum and field practices, limited training for educators, as well as the influence of unsupportive social environments often become the main barriers. In addition, technological development and globalization also bring new challenges, such as exposure to values that conflict with local culture. Therefore, understanding these obstacles is a crucial first step in designing effective strategies to strengthen character education in order to shape a generation that is morally and intellectually superior. The approach applied in this study is a qualitative approach. A qualitative approach serves as a research method that produces descriptive data in the form of writings or speech from individuals as well as observable behavior. Based on the results of the research conducted by the researcher regarding the obstacles teachers face in integrating character values into economic subject learning, these include the students' inherent character, the facilities and infrastructure available at the school, and most importantly, teachers do not yet understand how to instill character values into the teaching and learning process.